Penataan Perkotaan dan Marginalisasi Sektor Informal - Author: Sudarsono (Unisia, 2006)
The informal sector denotes a sector that plays irnportant role in term of Indonesian economical building. According to Bird Pusat Statistik, informal sectorsupports about 74 % toward vacation in 1985, decreases 72 % in 1990, and 65 % in 1998. These decreases mean that informal sector constitutes eccept dominant young worker. In stead, after economy crises, it is predicted the acceptance of young workers tend to increase. But, this important role, the discourse about informal sector more tends to show the problem than to solve it. This happens because of the lack of the correct limitation of informal sector.